Macroeconomic and financial stability in a monetary union: the case of Lithuania - Rubio, Margarita; Comunale, Mariarosaria (Elsevier, 2018)
In this paper, we study the implications for macroeconomic and financial stability of macroprudential policies in a monetary union. With this purpose, we develop a two-country monetary union new Keynesian general equilibrium model with housing and collateral constraints, to be calibrated for Lithuania and the rest of the euro area. We consider two different scenarios for macroprudential policies: one in which the ECB extends its goals to also include financial stability and a second one in which a national macroprudential authority uses the loan-to-value ratio (LTV) as an instrument. Results show that both rules are effective in bringing a more stable financial system in both countries, and especially in Lithuania. This is because the financial sector in this country is more sensitive to shocks. We find that an extended Taylor rule is indeed effective in reducing the volatility of credit but it comes with a cost in terms of higher inflation volatility. The simple LTV rule on its side, does not compromise the objective of monetary policy. This reinforces the "Tinbergen principle" which argues that there should be two different instruments when there are two different policy goals.